National Evaluation of the Enforcing Underage Drinking Laws Program - Law Enforcement Agency (LEA) and Youth Surveys, (United States), 1999-2005 - Wolfson, Mark ([Verlag nicht ermittelbar], 2018)
The Enforcing Underage Drinking Laws (EUDL) Program was designed to reduce the number of alcoholic beverages sold to and consumed by minors under the age of 21 by distributing grants to state agencies to increase law enforcement activity with regard to the sale of alcohol to minors. The main elements of the National Evaluation of the Enforcing Underage Drinking Laws Program are: Law Enforcement Agency (LEA) Survey: a telephone survey of law enforcement agencies in a sample of communities in states receiving discretionary grants, and Youth Survey: a telephone survey of youth, age 16 to 20, in these same communities. Each of these data collection efforts was conducted once relatively early in the implementation of the program and annually for two years thereafter for each round. The evaluation involves a comparison of communities that are receiving the most intensive "interventions"--in this case, communities that received sub-grants under the three rounds EUDL discretionary grant program--with communities that are not receiving such intense interventions.